COLOR REMOVAL FROM TEXTILE WASTEWATER WITH FENTON PROCESS - Gurtekin, Engin; Sekerdag, Nusret (Yildiz Technical Univ, 2008)
In this study, the color removal alternative from textile wastewater with Fenton process was determineted. The effects of factors such as pH, temperature, reactives (Fe2+ and H2O2), wastewater composition and Fenton-like processes in color removal with Fenton process have been investigated. As compared to the other advanced oxidation process, higher color removals with Fenton process have been obtained. Fenton process have an attractive importance in the color removal from textile wastewater because of the low costs, the lack of toxicity of the reagents (Fe2+ and H2O2), the absence of mass transfer limitation due to its homogeneous catalytic nature and the simplicity of the technology.
Keywords: Textile wastewater; Fenton process; color removal; advanced oxidation processes